Clinical Epidemiology and Molecular Investigation of Protoparvovirus carnivoran1 Infection in Naturally Infected Domestic Cats in Bangladesh - Sanjida Ali Sani; Chandan Nath; Md Moktadir Billah Reza; Jannatul Naima; Partha Samanta; Md Saddam Hossain; Md Rayhan Faruque; Md Ahaduzzaman (Veterinary Medicine and Science)
ABSTRACT Background The infection of cats with Protoparvovirus carnivoran1 is a global concern due to the likelihood of infection from multiple genetically similar viruses. Objectives The present study was undertaken to investigate the clinico‐molecular epidemiology of Protoparvovirus carnivoran1 infection in naturally infected domestic cats in Bangladesh. Methods Rectal swabs (N = 100) were collected from cats manifesting clinical signs and screened for the presence of Protoparvovirus carnivoran1 using polymerase chain reaction (PCR). Selected positive samples (n = 38) were partially sequenced for molecular analysis. A structured questionnaire was developed to estimate potential risk factors for Protoparvovirus carnivoran1 infection, clinical and therapeutic outcomes and overall associations among the variables. Data were analysed using descriptive, univariable and multivariable statistical techniques. Results The overall PCR detection rate of the targeted Protoparvovirus carnivoran1 virus was 99% (99/100). Young and non‐vaccinated animals were mostly infected (p < 0.05). The mortality and case fatality of infected cats were 10% and 45%, respectively. The clinical outcomes did not vary between animals receiving different therapeutic groups (p = 0.19). The phylogenetic analysis suggests that Protoparvovirus carnivoran1 isolates share a common ancestor with isolates from different global regions. Conclusions The findings indicate that Protoparvovirus carnivoran1 is circulating in Bangladesh. The clinico‐epidemiological and evolutionary outcomes can be used as a guide for future preventive and control measures against parvovirus infection, both locally and internationally.